Ray S. Cline papers - Cline, Ray S.
Office files consisting of calendars, interviews, press clippings, and judicial and congressional testimony relating to the organization and effectiveness of the U.S. intelligence community in the 1970s; organization files documenting Cline's association chiefly with the Georgetown University Center for Strategic and International Studies and also with Coalition for Asian Peace and Security and the World Strategy Network; addresses, briefings, lectures, and papers delivered at conferences and meetings; and drafts and published versions of articles, stories, and other writings by Cline. Topics include American, Chinese, Korean, and Soviet intelligence activities and national security concerns during the 1970s and 1980s. Also includes Cline's memorandum on the wartime of history of the Office of Strategic Services, forerunner of the CIA.
Corrrespondents include George Bush, Chiang Ching-kuo, Ho Shai-lai, Ernest W. Lefever, Clare Boothe Luce, Constantine Christopher Menges, and Arthur M. Schlesinger. The Cline-Schlesinger correspondence reflects both men's views on the Bay of Pigs and the invasion of Cuba (1961), although Cline's office files on the subject have been retained by the Central Intelligence Agency.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Analyst employed by the U.S. Central Intelligence Agency, educator, and author. Full name: Ray Steiner Cline. Born 1918; died 1996.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bush, George, -- 1924- -- Correspondence; Chiang, Ching-kuo, -- 1910-1988 -- Correspondence; Ho, Shai-lai -- Correspondence; Lefever, Ernest W. -- Correspondence; Luce, Clare Boothe, -- 1903-1987 -- Correspondence; Menges, Constantine Christopher -- Correspondence; Schlesinger, Arthur M. -- 1917-2007 -- Correspondence; Coalition for Asian Peace and Security; Georgetown University. -- Center for Strategic and International Studies; United States. -- Central Intelligence Agency; United States. -- Office of Strategic Services; World Strategy Network; Intelligence service -- China; Intelligence service -- Korea; Intelligence service -- Soviet Union; Intelligence service -- United States; National security -- United States; World War, 1939-1945 -- Secret service -- United States; Cuba -- History -- Invasion, 1961.; Authors; Educators; Intelligence analysts